1996
DOI: 10.1111/j.1365-3156.1996.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Health education for community‐based malaria control: an intervention study in Ecuador, Colombia and Nicaragua

Abstract: A malaria study was undertaken in 98 rural communities of the Pacific coast of Ecuador (n= 14), Colombia ( n = z z ) and Nicaragua (n=62). In-depth interviews on people's knowledge and practice regarding malaria aetiology, symptoms and treatment were conducted and complemented by formal household interviews. On the basis of this information, an educational programme was set up which included the training of village health promoters and community workshops organized by the health workers and used a set of metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
6
30
0
Order By: Relevance
“…Measures to promote appropriate health-seeking for the control of malaria should involve educational activities directed at caretakers and drug vendors, the effectiveness of such a training has been recorded for caretakers [46,47] and drug vendors [42,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Measures to promote appropriate health-seeking for the control of malaria should involve educational activities directed at caretakers and drug vendors, the effectiveness of such a training has been recorded for caretakers [46,47] and drug vendors [42,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a positive correlation between health education and the efficacy of treatment (Kroeger, Meyer, Mancheno, & Gonzalez, 1996). During 1970s and the 1980s, malaria was reasonably well controlled due to high awareness among the population and the use of intermittent preventative treatment (IPT) practices (antenatal administration of sulfadoxine-pyrimethamine drug and mosquito nets) to treat and prevent malaria among children (Paul et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The disease has a higher prevalence among those that are immunocompromised, often including children and pregnant women. One of the largest barriers inhibiting malaria treatment is a lack of education and literacy, which has caused misconceptions about disease development and prevention (Kroeger et al, 1996). Consequently, there has been overuse and misuse of malaria drugs due to self-diagnosis and self-prescription, a practice that has rendered cheaper drugs such as chloroquine and sulphadoxine-pyrimethamine ineffective (Opiyo et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more children under five years and older children slept under LLINs the night preceding the end line survey. These improvements are likely to have been encouraged by the education and awareness campaign that stressed the complementary nature of SolarMal, as other studies of effects on educational interventions on malaria control have shown happens in the short term (Kroeger, Meyer et al 1996;Amoran 2013). The improvements are also likely to have been further enabled by the availability of more LLINs at end line following a mass distribution campaign in August of 2014, 10 months before the end line survey commenced.…”
Section: Discussionmentioning
confidence: 99%